172 Two mutations, one patient: which phenotype?. (8th December 2021) - Giovannetti, Alessandro; Accietto, Antonella; Caponetti, Angelo Giuseppe; Saturi, Giulia; Ponziani, Alberto; Massa, Paolo; Sguazzotti, Maurizio; Longhi, Simone; Galiè, Nazzareno; Gagliardi, Christian
Abstract: Methods and results: Woman, 55 years old, she has as comorbidity high blood pressure and mild obesity. She came at our attention to perform screening cardiological exams after her brother, who was affected by amyloidotic TTR-related cardiomyopathy with Val30Met mutation, died for sudden cardiac death. At the first evaluation the patient is completely asymptomatic, she has not angor, dyspnoea and heartbeat. The ECG and echocardiography were negative for amyloidotic signs of heart involvement. The Tc-99-DPD scintigraphy showed no cardiac uptake (visual score = 0). To complete the diagnostic path the patient had been evaluated by a neurologist with electromyography, which was negative, and genetic test, which confirmed the presence of Val30Met mutation of TTR-gene. For this last outcome we decided to follow the patient at our clinics. In the following years the patient developed a progressive reduction of exercise tolerance and symmetric negative T waves in anterolateral and inferior lead at ECG. The echocardiogram showed a progressive medio-apical septal hypertrophy. To exclude an ischaemic cause the patient made a stress myocardial scintigraphy, which was negative for ischaemic signs, and she underwent to cardiac MRI which showed a septal thickness of 16 mm without amyloidotic radiological signs in T1-weighted and LGE sequences. For this reason, we suspected that the patient had a hypertrophic cardiomyopathy and she had been undergone another time to genetic test which confirmed the Val30Met TTR-mutation and MYBPC3 mutation. Usually, this last gene mutation for myosin binding protein C is associated with late-onset hypertrophic cardiomyopathy. Into account the new diagnosis and her sudden cardiac death family history we calculated the patient's HCM-risk score which was under 4%, so that we did not undergo the patient to ICD implantation. Conclusions: The case report is a rare example of coexistence of the transthyretin gene mutation and myosin binding protein C in the same patient. In this case to perform a correct diagnosis, it is crucial use an integrated multimodal approach including ECG, echocardiography and cardiac MRI.